(untitled) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 1993)
In the classical sections of Sentino-Valdorbia, Bosso and the Marne di Monte Serrone type-section the rhythmic, limestone/marl sedimentation of the following formations were studied: the Corniola (Late Sinemurian to Earliest Toarcian) and the Marne di Monte Serrone (Early Toarcian). The geological framework is drawn from the numerous and significant published papers which give a good stratigraphical scheme and a precise paleogeographic setting. The limestones have been studied in thin sections (texture, occurrence and abundance of schizospheres, other fauna, etc.) and with SEM (structure, occurrence, abundance and diagenetic state of schizospheres; coccoliths). Marly interbeds have been studied in light microscopy on smear slides of raw sediment to find out coccoliths and schizospheres and with SEM, both on washed and centrifuged sediments (for a better definition of the nannofloras) and on freshly broken surfaces. The conclusions are based upon 69 SEM pictures of limestones and 94 SEM pictures of marls from the Corniola Formation; on 169 SEM pictures of limestones and 303 SEM pictures of marls from the Marne di Monte Serrone Formation. The observations show the importance of the nannofloral contrast between the Limestone beds with schizospheres and the marly interbeds with coccoliths. The contrast is thought to portray rhe original difference between the components which generated the two different types of sediments. The lithogenetic role of the nannoplankton was strongly differentiated and was linked to an alternation of clay-poor, sea-warer phases when stable, calcareous nannoplankton (schizospheres) dominated and did not evolve and of clay-richer, sea-water phases when coccolithophorids expanded and evolved.